Education and psychology in interaction : working with uncertainty in interconnected fields - Norwich, Brahm (Routledge research in education., 2000)
The author takes an in-depth look at how these subjects relate to each other and at the current state of this relationship. He develops the theme that despite differences in aims, education and psychology are interconnected.